Shooting at the Wounded at Socijalno Junction
The footage shows the attack on a civilian truck and attempts by the passengers to escape. Parts of this footage are seen in many other tapes; this is original and complete footage. "Socijalno," Elektroprivreda and Vodoprivreda buildings shown burning. Benefit video/recording for Sarajevo by recording artist with a video clip at the end.